2006
DOI: 10.1108/02640470610707240
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge‐based mobile learning framework for museums

Abstract: Purpose -The purpose of this study is to propose a knowledge-based mobile learning framework that integrates various types of museum-wide content, and supports ubiquitous, context-aware, personalized learning for museums. Design/methodology/approach -A unified knowledge base with multi-layer reusable content structures serves as the kernel component to integrate content from exhibitions for education and collection in a museum. The How-Net approach is adopted to build a unified natural and cultural ontology. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 13 publications
0
26
0
Order By: Relevance
“…In many science museums and centres, the rapid evolution of information and communication technologies have replaced the role of humans in facilitating children's learning (Cheng et al 2011;Murriello and Knobel 2008;Hsu et al 2006). As a result, multiple and overlapping interactivity types are occurring with child-technology (see Fig.…”
Section: Science Museumsmentioning
confidence: 99%
See 1 more Smart Citation
“…In many science museums and centres, the rapid evolution of information and communication technologies have replaced the role of humans in facilitating children's learning (Cheng et al 2011;Murriello and Knobel 2008;Hsu et al 2006). As a result, multiple and overlapping interactivity types are occurring with child-technology (see Fig.…”
Section: Science Museumsmentioning
confidence: 99%
“…1). For example, Hsu et al (2006) demonstrated that a child-technology-environment interaction occurred when mobile phones were employed to help to improve elementaryschool children's learning in a science museum. In this study, the pre-visit learning stage included creation of a learning plan by specifying the student's subjects of interest, visit date and duration of stay.…”
Section: Science Museumsmentioning
confidence: 99%
“…The use of mobile technologies in education helps learners acquire the right content, at the right time and at the right place (Wagner, 2005;Waycott, Jones, & Scanlon, 2005). In addition, the use of mobile devices encourages and supports learning opportunities (Hsu et al, 2006) through relevant forms of access to information (Smordal & Gregory, 2003) and assessment tools for students (Kneebone et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…These vary from simple systems relying solely on device content adaptation [42], to complex infrastructures for generating context aware mobile learning applications [43]. Yarandi et al [44] have developed a mobile learning system with four modules to enable courseware management, course content adaptation, test evaluation and course recommendation mediation.…”
Section: Background and Related Workmentioning
confidence: 99%
“…Unlike the systems described above, Mobilearn [43] is a complete infrastructure developed by a consortium of European universities in collaboration with MIT and Stanford to build mobile learning applications. Mobilearn is based on the Open Mobile-access Abstract Framework (OMAF).…”
Section: Background and Related Workmentioning
confidence: 99%